The Navigation of Afrocentricism in Countee Cullen’s “Heritage” and Incident”: The Poetics of Identity (Bon Voyage, 2019)
This paper brings forward the course and determination of Afro-American people toward their origin as experienced by African Americans. It remarkably remaps the poetics of identity amid the racial segregation as projected in Countee Cullen’s “Heritage” and “Incident.” Further, it deals with the color line discrimination over enslaved community and fabricated knowledge about their history as problematic of research. Because the slavery system has belittled Afro-Americans and alienated them from their atavistic culture so that they fail to enjoy human dignity and identity. My purpose, here, is to delve into the issue of color discrimination that not only hems the Afro- American community but also dislocates them from their heritage. Largely, this paper navigates their alienated position amid the vast opportunities of material progress in America. Moreover, this paper intends to go through the genealogical studies of the race as envisioned by Paul Gilroy and W.E.B. Du Bois who advocate for enslaved community’s dignity and identity. Admittedly, genealogical history of the race takes the Afro-American people back to the time before ‘the slave trade’ era when they were happy and free enjoying their culture and language with human dignity in their atavistic land, Africa.